Minimally Invasive Cardiac Surgery - Dhaliwal, RS (Journal of Universal College of Medical Sciences, 2013)
Conventional open heart surgery on cardiopulmonary bypass although safe and effective, but is associated with definite morbidity and mortality due to deleterious effects on body systems like haematological, renal, hepatic, respiratory and nervous system. In the last two decades minimally invasive cardiac surgery is rapidly emerging as a safe and cost effective alternative therapeutic modality. The aims of minimally invasive cardiac surgery are to achieve an early extubation, less blood loss, rapid recovery, shorter hospital stay, less patient morbidity, faster return to routine activity, increased patient comfort and low cost without compromising on the results. Various strategies have been developed to avoid cardio-pulmonary bypass, global myocardial ischemia and hypothermia. Minimally invasive cardiac surgery is especially beneficial in patients who are at high risk due to left ventricular dysfunction, calcified aorta, carotid artery occlusion, bleeding diathesis and impaired renal dysfunction DOI: http://dx.doi.org/10.3126/jucms.v1i3.8769 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 62-66